2021
DOI: 10.1016/j.ejca.2020.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the age gap in breast cancer. Impacts of omission of breast cancer surgery in older women with oestrogen receptor positive early breast cancer. A risk stratified analysis of survival outcomes and quality of life

Abstract: Background: Age-related breast cancer treatment variance is widespread with many older women having primary endocrine therapy (PET), which may contribute to inferior survival and local control. This propensity-matched study determined if a subgroup of older women may safely be offered PET. Methods: Multicentre, prospective, UK, observational cohort study with propensity-matched analysis to determine optimal allocation of surgery plus ET (SþET) or PET in women aged !70 with breast cancer. Data on fitness, frail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…3). 87 The median age of this matched cohort was 82 to 83, with higher rates of frailty and comorbidity than the general population.…”
Section: Achieving Health Equity Among Older Adults: a Surgical Oncologist's Perspectivementioning
confidence: 96%
See 2 more Smart Citations
“…3). 87 The median age of this matched cohort was 82 to 83, with higher rates of frailty and comorbidity than the general population.…”
Section: Achieving Health Equity Among Older Adults: a Surgical Oncologist's Perspectivementioning
confidence: 96%
“…The key is to select older women with a predicted life expectancy of fewer than 3 to 5 years for primary endocrine therapy. The Age Gap observational cohort Reproduced with permission from Wyld et al 87 study attempted to define the health characteristics of women suitable for primary endocrine therapy by recruiting women older than age 70 with early breast cancer and adjusting for baseline health and fitness using detailed propensity score matching. The study found that when matched cohorts with similar health status treated with either surgery or primary endocrine therapy were compared, there was no survival advantage with surgery (Fig.…”
Section: Achieving Health Equity Among Older Adults: a Surgical Oncologist's Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Bridging the age gap Phase 1 showed that older patients (70-95 years) undergoing breast cancer surgery experienced a long-term negative impact on QOL and independence up to 2 years [14] For ER? breast cancer, patients who underwent either S?ET or PET both exhibited a decline in global health status scores, with a sharper decline in the surgery group at 6 weeks and failure to return baseline [1] Nottingham Research Programme Updated findings were conflicting, showing areas of improvement related to FS and a decline in others. No clear pattern was identified [16] ALND.…”
Section: Activities Of Daily Livingmentioning
confidence: 99%
“…Surgery is the recommended treatment option for primary breast cancer irrespective of age. Primary endocrine therapy (PET) may be an alternative in selected older patients with significant comorbidities, as the overall survival benefit observed with surgery in certain subtypes of breast cancer may prove to be minimal when life expectancy is limited by other comorbidities [ 1 , 2 ]. Furthermore, a survey involving surgical oncologists published by Ghignone et al [ 3 ] highlighted that quality of life (QOL) and recovery of functional status (FS) were considered the most pertinent outcomes in onco-geriatric surgery, rather than overall survival.…”
Section: Introductionmentioning
confidence: 99%